1994
DOI: 10.1177/101053959400700104
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Factors Associated with Intestinal Parasites Among Children Living in Gombak, Malaysia

Abstract: Fecal specimens collected from 456 school children in Gombak, Malaysia, revealed an overall prevalence rate of 62.9%. The most common parasite found was Trichuris trichiura (47.1%) followed by Giardia intestinalis (14.7%), Entamoeba coli (11.4%), Entamoeba histolytica (9.9%) and Ascaris lumbricoides (7.9%). Infection rates were high among the Indonesian immigrant workers' children (90%) followed by the Orang Asli (79.5%), Malay (59.4%) and Indians (36.4%). Females (66.3%) had a higher prevalence rate than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 2 publications
1
16
1
Order By: Relevance
“…Given its faecal-oral route, habits related to eating, defecation, personal hygiene, cleanliness and level of education may have an impact on the prevalence rates. The findings of this study confirmed a trend of high risk of infection with Entamoeba species among the rural population as shown by other local studies [21-23,25], where prevailing poverty, poor socioeconomic condition, low standards of sanitation and hygiene and lack of education attainment may contribute to high prevalence of Entamoeba infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Given its faecal-oral route, habits related to eating, defecation, personal hygiene, cleanliness and level of education may have an impact on the prevalence rates. The findings of this study confirmed a trend of high risk of infection with Entamoeba species among the rural population as shown by other local studies [21-23,25], where prevailing poverty, poor socioeconomic condition, low standards of sanitation and hygiene and lack of education attainment may contribute to high prevalence of Entamoeba infection.…”
Section: Discussionsupporting
confidence: 91%
“…Another study showed that the infection rate of Entamoeba in rural communities in Malaysia was 21.0% [24]. Other local studies which include aboriginal groups reported prevalence ranging from 9.4% to 18.5% [25,26]. However, these prevalence rates were based on microscopic examination which could not differentiate between E. histolytica E. dispar and E.moshkovskii infections.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the current finding highlighted that the infection of T. trichiura to be the highest among Temuan (46.2% of 171). Some reasons that have been pinpointed by other studies in Malaysia included that T. trichiura possesses higher rate of infections due to its resistance to anthelminthics, ineffective dosage and choice of anthelminthic used [1], [2], [29], [30]. Local studies showed that a single dose (400 mg) of albendazole was proven ineffective to kill T. trichiura [29]–[31].…”
Section: Discussionmentioning
confidence: 99%
“…Some reasons that have been pinpointed by other studies in Malaysia included that T. trichiura possesses higher rate of infections due to its resistance to anthelminthics, ineffective dosage and choice of anthelminthic used [1], [2], [29], [30]. Local studies showed that a single dose (400 mg) of albendazole was proven ineffective to kill T. trichiura [29]–[31]. Instead, increased doses of albendazole were required in order to obtain higher cure rate among the infected persons [1], [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation